2021
DOI: 10.3390/ma14175100
|View full text |Cite
|
Sign up to set email alerts
|

Performance of MoS2/Zr Composite Coatings at Different Deposition Temperatures

Abstract: The properties of the MoS2/Zr coatings can be significantly affected by the deposition temperature. In this study, the MoS2/Zr composite coatings were fabricated on the cemented carbide surface, utilizing the duplex deposition technology at various deposition temperatures. The effects of deposition temperature on the mechanical and friction properties of the MoS2/Zr coatings were systematically studied. Results exhibited that as the deposition temperature increased, the adhesion force increased first and then … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…On the other hand, multi-layer coatings offer benefits compared to single-layer coatings. One commonly used multi-layer coating is TiAlN/ AlCrN [9], which combines the properties of both TiAlN and AlCrN coatings. These multi-layer coatings have been found to outperform others when it comes to tool steel performance.…”
Section: Coating Materials and Their Propertiesmentioning
confidence: 99%
“…On the other hand, multi-layer coatings offer benefits compared to single-layer coatings. One commonly used multi-layer coating is TiAlN/ AlCrN [9], which combines the properties of both TiAlN and AlCrN coatings. These multi-layer coatings have been found to outperform others when it comes to tool steel performance.…”
Section: Coating Materials and Their Propertiesmentioning
confidence: 99%
“…In addition, the quality of the coatings is affected by multiple parameters (sputtering power, target distance, matrix bias, deposition temperature, etc.). For example, W. Song used the biphase deposition method to prepare MoS 2 /Zr composite films at different temperatures and found that appropriate preparation temperatures (180~200 • C) give the films excellent tribological properties [22]. J.…”
Section: Introductionmentioning
confidence: 99%